Analysis of Learning Interests and Student Responses in Online Learning Using E-Learning - Mellyta Uliyandari Uliyandari; Nurlia Latipah; Dewi Handayani (STAI Hubbulwathan Duri, 2021)
This study aims to analyze interest in learning and student responses in online learning using e-learning media in Universitas Bengkulu. The method used in this research is descriptive qualitative. Data collection was carried out using a questionnaire distributed using google form. Questionnaire analysis was carried out using a mini step application with the Rasch model. The population in this study was 193 science education students with a total sample of 64 people. The results showed that the interest in learning science education students in general chemistry 2 had a conversion value of 78.56, which was in the high category. Meanwhile, the student person towards online learning using e-learning media also showed good results, with a conversion value of 60.42, which was in the good category.